Disrupting the brain to validate hypotheses on the neurobiology of language - Papeo, Liuba; Pascual-Leone, Alvaro; Caramazza, Alfonso (Frontiers in Human Neuroscience, 2013)
Comprehension of words is an important part of the language faculty, involving the joint activity of frontal and temporo-parietal brain regions. Transcranial Magnetic Stimulation (TMS) enables the controlled perturbation of brain activity, and thus offers a unique tool to test specific predictions about the causal relationship between brain regions and language understanding. This potential has been exploited to better define the role of regions that are classically accepted as part of the language-semantic network. For instance, TMS has contributed to establish the semantic relevance of the left anterior temporal lobe, or to solve the ambiguity between the semantic versus phonological function assigned to the left inferior frontal gyrus. We consider, more closely, the results from studies where the same technique, similar paradigms (lexical-semantic tasks) and materials (words) have been used to assess the relevance of regions outside the classically-defined language-semantic network – i.e., precentral motor regions – for the semantic analysis of words. This research shows that different aspects of the left precentral gyrus (primary motor and premotor sites) are sensitive to the action-non action distinction of words’ meanings. However, the behavioral changes due to TMS over these sites are incongruent with what is expected after perturbation of a task-relevant brain region. Thus, the relationship between motor activity and language-semantic behavior remains far from clear. A better understanding of this issue could be guaranteed by investigating functional interactions between motor sites and semantically-relevant regions.